Figuring Out Fertilizer for the Home Lawn - Laurie E. Trenholm; Joseph B. Unruh (EDIS, 2004)
Applying the correct amount of fertilizer to your home lawn is critical for two reasons. The first is that the health and vigor of your lawn depends upon applying the right amount of fertilizer, with too little or too much fertilizer causing problems for the growth, appearance, and health of your lawn. The second is that improper application of fertilizer can harm the environment. Over-application or misapplication of fertilizer can potentially result in leaching of chemicals through the soil into ground water supplies or run-off of chemicals into surface water. On the other hand, applying too little fertilizer may result in a lawn with minimal density of root and shoot systems, which will allow for leaching to occur more readily. Since this is an important environmental issue, we need to ensure that we handle fertilizers properly and apply the correct amounts when we fertilize. This document is ENH962, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 9, 2003.